Patient characteristics of medical encounters at the Olympic Stadium during the Tokyo 2020 Olympic and Paralympic games - Sekizaki, Yumiko; Hiden, Akina; Yamamoto, Ryo; Nishida, Yusho; Kondo, Akihiko; Takami, Hiroki; Toyomoto, Yoichi; Ishida, Hiroyuki; Watanabe, Shin; Sasaki, Junichi (Frontiers in Public Health, 2025)
ObjectiveMass gatherings challenge local healthcare systems due to increased spectator demands. During the Tokyo 2020 Olympic and Paralympic Games, a medical team stationed at the Olympic Stadium implemented an on-site medical system for over 3,000 nonathlete attendees. This study analyzed medical encounters among nonathlete participants and evaluated the system’s effectiveness.MethodsA retrospective descriptive analysis was conducted, reviewing medical records from the on-site medical suite at the Tokyo 2020’s main stadium and from hospitals to which patients were transferred. Data included patient demographics, symptoms, vital signs, diagnoses, treatments, and response times both on-site and at hospitals.ResultsOf the 44 patients included, heat-related illness and trauma were the most frequent conditions. Seven (15.9%) patients required hospital transport. Median times recorded were 22 min to the on-site suite, 51 min under the on-site care, and 66 min of prehospital time.ConclusionThe availability of specialized physicians and nurses facilitated efficient triage and early treatment within the on-site setting. This study underscores the importance of medical preparedness for future large-scale gatherings.